Kokoda Muslim Community Empowerment: A Social Intervention in Sorong City, West Papua - Andi Ahriani; Anita Candra Dewi (International Journal of Sustainable Applied Sciences, 2023)
Muslims in Kokoda have a reputation for being economically disadvantaged and technologically illiterate. Despite the fact that they are well-known to possess advantageous cultural assets and natural resources that can be utilized to enhance their standard of living. Consequently, the Kokoda Muslim community in Sorong City, West Papua, will be the focus of this research as it examines the theoretical tactics and concepts of empowerment-based social intervention. In order to help people live better and be more self-reliant, this course will explain social intervention and community empowerment in general and then propose theoretical solutions for interventions that are based on empowerment. A theoretical technique of empowerment-based social intervention, R-O-N (Resources, Organizing and Norms), was discovered as a result of this research.